POLITIK HUKUM PEMBENTUKAN UNDANG-UNDANG PERLINDUNGAN SAKSI DAN KORBAN, DILIHAT DARI PERLINDUNGAN WHISTLEBLOWER (SAKSI PELAPOR) DAN SAKSI AHLI DI INDONESIA - Aris Irawan (JURNAL AKTA YUDISIA, 2020)
Abstract The configuration of legal politics always influences the development (character) of legal products. democratic political configurations always give birth to responsive character laws, the Eradication and Prevention Policy on Corruption, Collusion and Nepotism, which states that there is a need for a law regulating witness protection. In the light of the Witness and Victim Protection Act, it turns out that the law on the protection of witnesses and victims in terms of legal politics has not yet been able to meet the needs of the community. There should have been a government policy in the form of a law to protect the reporting witnesses or also called the Whistleblower, as well as expert witnesses, meaning that the existing laws are not in accordance with community needs (not responsive to community development) Keywords: Politics of Law, Legal Protection, Reporting Witness, Expert Witness